Paediatric outcomes and timing of admission. Issue 6 (15th March 2018) - Ramsden, Louise; McColgan, Martin Patrick; Rossor, Thomas; Greenough, Anne; Clark, Simon J
Abstract : Studies of adult patients have demonstrated that weekend admissions compared with weekday admissions had a significantly higher hospital mortality rate. We have reviewed the literature to determine if the timing of admission, for example, weekend or weekday, influenced mortality and morbidity in children. Seventeen studies reported the effect of timing of admission on mortality, and only four studies demonstrated an increase in those admitted at the weekend. Meta-analysis of the results of 15 of the studies demonstrated there was no significant weekend effect. There was, however, considerable heterogeneity in the studies. There were two large UK studies: one reported an increased mortality only for planned weekend admissions likely explained by planned admissions for complex conditions and the other showed no significant weekend effect. Two studies, one of which was large (n=2913), reported more surgical complications in infants undergoing weekend oesophageal atresia and trachea-oesophageal repair. Medication errors have also been reported to be more common at weekends. Five studies reported the effect of length of stay, meta-analysis demonstrated a significantly increased length of stay following a weekend admission, the mean difference was approximately 1 day. Those data, however, should be interpreted with the caveat that there was no adjustment in all of the studies for differences in disease severity. We conclude that weekend admission overall does not increase mortality but may be associated with a longer length of stay and, in certain conditions, with greater morbidity.